O ensino de ciências e a avaliação da aprendizagem: uma abordagem dialógica na escola pública por meio dos grupos interativos - Ferreira, José dos Santos (Universidade Federal Rural do Semi-Árido, 2020)
The relevance questioned by the dialogism worked in the Interactive Groups and their application at school, allows students to understand the transformations that occur in the physical world, of the acquired information or pre-established knowledge. The general objective of the research is understand the possible impacts caused by the educational praxis in force at school, based on the processes of evaluation of school learning, in the final years of elementary school, relating to dialogical learning, educational paradigms and traditional evaluative trends in Science teaching through Interactive Groups. For this, we follow a methodological path where we carry out a data survey through the production of two states of knowledge, investigating productions related to the problematic theme. We also carried out an Action Research and a Focus Group Interview, both applied to a class in the last year of elementary school. The research is classified as descriptive. Concerning the approach for the data collection, it was carried out in a qualitative way, making a dialogue with theorists who discuss dialogical learning as Vygotsky (1983, 1999, 2008), Freire (1983, 1996, 2001), Freire e Schor (1996), Flecha (1997), Ferrada e Flecha (2008), Braga, Gabassa e Mello (2010) e Braga e Mello (2014). Giving emphasis to evaluation with Luckesi (2000, 2011, 2013), Vasconcellos (1998), Perrenoud (1999) and to education. It was also given emphasis to science epistemology, with Santos (2003), Alves (2009) and to science teaching with Bizzo (2002), Cachapuz et al. (2005), Pozo and Crespo (2009), among others. Data were analyzed and discussed, following the content Analysis Approach by Bardin (2009, 2011), and were characterized in relation to the bibliographic and documentary content. The results suggest pertinence in guiding the evaluation processes, about science teaching, faithfulness in the characteristics attributed to educational levels in the final years of elementary school, interrelationship between paradigms and traditional trends with dialogic and interactive practices of learning assessment. They also suggest better student/student and teacher/student relationships, indicate possible paths to be followed based on evaluative methodologies that use interaction and dialogism, as among others results that may contribute to facilitate learning, to improve teaching, and the quality of basic education
Keywords: Avaliação da aprendizagem; Grupos Interativos; Aprendizagem dialógica; Learning evaluation; Interactive groups; Dialogic learning; MULTIDISCIPLINAR::ENSINO